A dynamic finite element procedure for bending collapse of composite thin-walled lenticular tubes. (1st May 2022) - Jia, Qilong; An, Ning; Ma, Xiaofei; Zhou, Jinxiong
Abstract: This paper presents an explicit dynamic procedure based finite element framework to investigate the quasi-static bending collapse behavior of composite thin-walled lenticular tubes (CTLTs). A detailed description of the boundary conditions and loads adopted for pure bending tests, and of determining appropriate analysis parameters that control the quasi-static process, such as the simulation time duration and damping coefficient, is given with simulation tests. The quasi-static condition is ensured by using energy balance assessments and the accuracy of the results is verified against true static simulation results reported previously. The collapse performances of a particular CTLT were evaluated numerically in two bending directions. Two distinct regimes were observed, namely, a pre-collapse regime and a post-collapse regime, and the collapse peak moment and critical bending angle that mark the division of the two regimes were predicted. It is shown that as the bending angle increases progressively, the CTLT first bends and buckles into periodic wrinkling patterns at the locally compressed region in the pre-collapse stage, and then after collapsing into the post-collapse stage, the bending moment drops rapidly and the wrinkling patterns evolve into localized ridges and folds, and finally the deformation is concentrated at a certain position of the compressed region.